2010
DOI: 10.1021/jp104485k
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics and Photochemistry of the UV Filter Kynurenine Covalently Attached to Amino Acids and to a Model Protein

Abstract: The photophysics and photochemistry of kynurenine (KN) covalently bound to the amino acids lysine, cysteine, and histidine, the antioxidant glutathione, and the protein lysozyme have been studied by optical spectroscopy with femto- and nanosecond time resolution. The fluorescence quantum yield of the adducts of KN to amino acids is approximately 2 times higher than that of the free KN in solution; KN attached to protein exhibits a 7-fold increase in the fluorescence quantum yield. The S(1) state dynamics of KN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Most likely, the IC mechanism of KNY is similar to that of KN and other UV filters, and includes transformation of the absorbed light energy into heat via hydrogen bond vibrations. 1,2,35 Photolysis of KNY in aqueous solution results in the formation of two intermediates, observed by nanosecond flashphotolysis, namely the KNY triplet state and the species which was attributed to the KNY enol form in the ground state, and of two products detected in the irradiated samples by HPLC, i.e. 4HQN and DHQN.…”
Section: Photophysics and Photochemistry Of Knymentioning
confidence: 99%
See 1 more Smart Citation
“…Most likely, the IC mechanism of KNY is similar to that of KN and other UV filters, and includes transformation of the absorbed light energy into heat via hydrogen bond vibrations. 1,2,35 Photolysis of KNY in aqueous solution results in the formation of two intermediates, observed by nanosecond flashphotolysis, namely the KNY triplet state and the species which was attributed to the KNY enol form in the ground state, and of two products detected in the irradiated samples by HPLC, i.e. 4HQN and DHQN.…”
Section: Photophysics and Photochemistry Of Knymentioning
confidence: 99%
“…The main deactivation pathway of the photoexcited UV filter in aqueous solutions is solvent-assisted internal conversion to the ground state, which proceeds with an efficiency of about 99%. 1,2 The "primary" UV filters, namely kynurenine (KN), 3-hydroxykynurenine (3OHKN) and 3-hydroxykynurenine O-β-D-glucoside (3OHKG), are synthesized enzymatically from tryptophan. [3][4][5][6] Under physiological conditions, these compounds can undergo spontaneous deamination 7,8 yielding highly reactive carboxyketoalkenes (CKAs), the subsequent reactions of the latter resulting in the production of "secondary" UV filters, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous studies of KN and its adducts, the solvent relaxation of KNs predominantly occurs in two stages: (1) diffusive motion of the solvent molecules around the excited UV filter molecule, typically ϳ1 ps in aqueous solution and (2) conformational changes of UV filter geometry in the excited state, approximately 4 to 10 ps, depending on the substituent. 21,24 The time resolution of the experiment is not sufficient for the inertial part of solvation, that takes place in Յ100 fs, to be resolved. In the case of 3OHKN, the solvent relaxation is hidden by the fast decay of the excited state population.…”
Section: Time-resolved Fluorescence Measurementsmentioning
confidence: 99%
“…Among the major UV filters found in the human lens, only the photochemistry of KN has been studied in detail, 11,14 -21 some data can be found on 3OHKN 14,17,19,[21][22][23] and glutathionyl-kynurenine 19,24 (GSH-KN), whereas the photochemical properties of 3OHKG and AHBG have not been reported yet. It has been shown that the S 1 lifetime of KN amounts to 30 ps in aqueous solutions, increases by more than one order of magnitude in alcohols, and exceeds 1 ns in aprotic solvents such as DMSO and DMF.…”
mentioning
confidence: 99%
“…Since these substances are more photochemically active than the original UV fi lters, they are responsible for the formation of active oxygen species promoting development of cataract with age [5]. The decrease of free, not protein-bound UV fi lters (KN, 3OHKG, 3OHKN) with age in lens tissue is ≈12% per decade [6].…”
mentioning
confidence: 99%